Strengthening Tobacco Consumption Control Policies: Program Integration for Social Assistance Recipients in Indonesia - Kusuma Hartono, Risky; Nurhasana, Renny; Satrya, Aryana; Rizky Ningtyas, Fadhilah; Oktarina, Ratih; Candaika, Putri; Madelif Sihombing, Isranalita (Jurnal Promkes: The Indonesian Journal of Health Promotion and Health Education, 2024)
Background: The prohibition on using social assistance funds for purchasing cigarettes has been stipulated in the Minister of Social Affairs Decree Number 175 of 2022. However, the primary goal of this program to improve community welfare is threatened as this misuse persists. Aims: This study aims to analyze the challenges and obstacles in implementing the policy to control cigarette consumption among social assistance recipients and to identify integrated priority programs across sectors. Methods: This qualitative study employs a case study approach. Data were collected through in-depth interviews and focus group discussions with informants representing central governments, regional governments, and social assistance officers. The interviews were then analyzed using SWOT analysis to formulate strategies and identify the priority program. Results: The analysis reveals that cross-sector collaboration is a key strength for reinforcing cigarette consumption control among the recipients. This is implemented through the Family Capability Improvement Meeting (P2K2), involving healthcare workers who educate the dangers of smoking and establish Smoking Cessation Service Clinics (UBM). The proposed priority program integrates the social assistance program with UBM clinics to help recipients quit smoking. Conclusion: The study concludes that strengthening this policy requires comprehensive program integration with multi-sector involvement. This enhancement also necessitates stronger central regulatory support through the Government Regulations as derived from Health Law Number 17 of 2023. Strengthening this policy is expected to contribute to achieving the SDGs by improving community health and quality of life, and alleviating poverty through improved effectiveness of the social assistance program.